2022
DOI: 10.1371/journal.pntd.0010478
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability and Aedes vector indices in the southern Philippines: An empirical analysis

Abstract: Background Vector surveillance is an essential public health tool to aid in the prediction and prevention of mosquito borne diseases. This study compared spatial and temporal trends of vector surveillance indices for Aedes vectors in the southern Philippines, and assessed potential links between vector indices and climate factors. Methods We analysed routinely collected larval and pupal surveillance data from residential areas of 14 cities and 51 municipalities during 2013–2018 (House, Container, Breteau and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The life cycle of mosquitoes is greatly influenced by meteorological conditions, and the mechanism of its influence has always been a subject of curiosity [3][4][5][6][7][37][38][39][40][41]. Our sensitivity analysis of these effects found that the aftermath duration of the impact of changing climate in different seasons on mosquito numbers was different.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 90%
See 1 more Smart Citation
“…The life cycle of mosquitoes is greatly influenced by meteorological conditions, and the mechanism of its influence has always been a subject of curiosity [3][4][5][6][7][37][38][39][40][41]. Our sensitivity analysis of these effects found that the aftermath duration of the impact of changing climate in different seasons on mosquito numbers was different.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 90%
“…The warm and humid climate of several coastal provinces in southern China is particularly suitable for the breeding of Aedes albopictus, the main vector of dengue fever, which inevitably increases the risk of dengue outbreaks [1,2]. Therefore, the characterization and prediction of the population dynamics of A. albopictus, especially the analysis of the impact of key climate factors on mosquito numbers (based on proxy values derived from two entomological indices), are of practical significance for the prevention and early warning of dengue outbreaks [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change has and will continue to cause more infectious disease transmission via affecting pathogen development, increasing vector growth rate, shortening the extrinsic incubation period, and changing human behaviour, 131 , 132 , 133 , 134 , 135 which leads to both spatial and temporal expansion of infectious disease cases. Many studies suggest that climate change with increased temperatures is causing more food-, water- and vector-borne disease cases in Australia.…”
Section: Climate Change Adaptation Measures and Activities In Australiamentioning
confidence: 99%